Computer Based Recitation Program Development With Feed Back in Newton’s Law Topic - Auna Hidayati, Rahma; Taqwa, Muhammad Reyza Arief (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research was conducted to develop a recitation program on Newton's law and to test its practicality. This type of research is Research and Development (R&D) with a Four-D (4D) model with stages, namely Define (defining), Design (design), Develop (development), and Dissemenate (dissemination). The research subjects were 38 third semester physics students at the State University of Malang. Data collection techniques were carried out by means of media validity test questionnaires and content validity tests given to 2 validator lecturers, as well as practicality test questionnaires and perception questionnaires on the use of each item given to students. The data generated is the percentage of the assessment of the validity test, practicality test, and student perception questionnaires, as well as suggestions given by lecturers and students related to the recitation program. This research resulted in a recitation program in which there were 38 questions accompanied by feedback. The results of the content validity test obtained a value of 95.7%, while the results of the media validity test obtained a value of 93.75% so that it was included in the very valid category. Then, the results of the practicality questionnaire show that students agree that the recitation program can make it easier to understand Newton's law concepts, help strengthen their understanding of Newton's law concepts, and this program is interesting for them. Meanwhile, based on the results of the student perception test regarding the use of items, the average score was 96.6%, which means that the questions, feedback, and discussion videos in the recitation program are very easy to understand.